The GSH responsive indocyanine green loaded PD-1 inhibitory polypeptide AUNP12 modified MOF nanoparticles for photothermal and immunotherapy of melanoma - Hao, Ying; Liu, Tailuo; Zhou, Hao; Peng, Jinrong; Li, Ka; Chen, Yuwen (Frontiers in Bioengineering and Biotechnology, 2023)
Photothermal therapy (PTT) holds significant potential for the treatment of malignant tumors. However, conventional single PTT often struggles to effectively inhibit tumor metastasis and recurrence. In this study, we constructed a MOF nanoparticle with a synergistic therapeutic effect combining photothermal and immunotherapy, enabling selective blocking of the PD-1/PD-L1 pathway within the tumor microenvironment.Firstly, MOF nanoparticles were synthesized using NH 2 -TPDC as ligands and Zr +4 as metal ions. Subsequently, NH 2 was modified to N 3 via azide transfer reagents. Through a copper free catalytic click chemical reaction, the PD-1/PD-L1 blocking agent AUNP-12 functionalized with disulfide bonds of DBCO was covalently introduced into MOF nanoparticles which were then loaded with the photothermal agent indocyanine green (ICG) to successfully obtain uniformly sized and stable ICG-MOF-SS-AUNP12 nanoparticles. ICG-MOF-SS-AUNP12 exhibited GSH-triggered release of PD-1/PD-L1 blockers while demonstrating potent photothermal effects capable of efficiently killing tumor cells. Under 808 nm near-infrared (NIR) irradiation, ICG-MOF-SS-AUNP12 effectively promoted the maturation of DC cells and activated immune responses. This study presents a novel method for constructing MOF-based nanodrugs and offers new possibilities for the synergistic treatment of tumors involving photothermal combined with immunotherapy.